Peran Motivasi Kerja dalam Memediasi Pengaruh Kompetensi Pedagogik dan Profesionalisme terhadap Kinerja Guru - Nadia Hani Sofiatussalma; Budhi Cahyono (Lembaga Yasin AlSys, 2026)
Teacher performance is a key factor in improving educational quality and is strongly influenced by internal aspects such as pedagogical competence, professionalism, and work motivation; however, at the junior secondary school level, suboptimal teacher performance is still found, particularly in the learning process. This study aimed to analyze the effects of pedagogical competence and professionalism on teacher performance, with work motivation as a mediating variable, based on students’ perceptions. A quantitative approach with an explanatory research design was employed involving students of SMP Walisongo Semarang, with a sample of 102 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed using multiple linear regression, path analysis, and the Sobel test. The results showed that pedagogical competence and professionalism had a positive effect on teacher performance. In addition, work motivation had a positive and significant effect on teacher performance and was proven to mediate the influence of pedagogical competence and professionalism on teacher performance. These findings indicate that improving teacher performance depends not only on competence and professionalism but also on strengthening work motivation, implying that efforts to develop pedagogical competence and professionalism need to be accompanied by strategies to enhance work motivation in order to support the quality of learning in schools.